PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI FRAKTUR FEMUR - Wahyuningsih; Sutanta; Vina Asna Afifah (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Fracture is a break of tissue continuity caused by trauma or physical exertion. Surgery or operative action is a management of fracture that can cause anxiety. One of therapy to reduce anxiety can use deep breathing relaxation techniques to reduce tension especially preoperative moment. Objective: To determine effect of deep breathing relaxation techniques on anxiety level of femur fracture preoperative patient in Karima Utama Surgical Hospital. Method: The type of research used quantitative research with a Quasi Experiment with Pre Test and Post Test Nonequivalent Control Group design. Sampling technique used Accidental Sampling as many as 30 respondents. Analysis data used Mann-Whitney test with confidence level of 95%. Result: Obtained P-value = 0.000 means there is a significant effect on the administration of deep breathing relaxation techniques on the anxiety level of femur fracture preoperative patients. Conclusion: There was a significant effect on the administration of deep breathing relaxation techniques on the anxiety level of femur fracture preoperative patients in the Karima Utama Surgical Hospital.